PENGARUH WARNA NAUNGAN PLASTIK DAN DOSIS PUPUK ORGANIK KOMPOS TERHADAP PERTUMBUHAN BAWANG MERAH (Allium ascalonicum L.) - Iskandar Umari; Wiwit Widarti; Insan Wijaya; Hudaini Hasbi (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2018)
The aim of the research was to study the effect of calors plastic shade and dosage organic fertilizer and the interaction on the growth analyze of Shallots. The experiment was conducted in experiment field of Agriculture Faculty, University Muhammadiyah of Jember.The experiment was arranged in Randomized Block Design consisted of 4 x 3 factorial treatments with three replications. The first factor were 3 levels of Transparent Plastic Shelter, i.e.: clear, blue, and red. The second factor were 4 levels of compost organic fertilizer application, i.e.: 15, 20, 25 and 30 t/ha. The results showed a significant interaction between the color shade of plastic and a dose of organic fertilizer on the parameters of leaf area age 60 days after planting and leaf area index age 60 days after planting, treatment shade of blue with organic fertilizer 30 tons / ha showed the best effect on leaf area and treatment shade of blue with dosages of 25 tons / ha showed the best effect on leaf area index. Use of shade of blue give the best effect on leaf area age 60 hst and shade of red gives the best effect on the growth rate of plants. The treatment dose of organic fertilizer 25 tons / ha gives the best effect on leaf area index age of 60 days after planting, the rate of plant growth, and relative growth rate, and treatment with a dose of fertilizer 30 ton / ha.